UNECE Nexus: Sustainable Mobility and Smart Connectivity - United Nations Economic Commission for Europe (United Nations, 2021)
This publication reviews the challenges to and vital importance of mobility and connectivity within the ECE region, highlighting their role in the operation of an economy and in moving goods and people within and across borders. It further demonstrates that the digitalization of many of these processes is key to improving efficiency and effectiveness, also addressing the main challenges in these two areas. Understanding such challenges is fundamental to assisting Member States in achieving the Sustainable Development Agenda, as each country has related actions to pursue. In the context of the COVID-19 pandemic, adequate mobility and connectivity have been shown to be fundamental to the correct functioning of medical care and the economy, without which vital medical relief and supplies cannot reach those most in need. A shift to more sustainable mobility, coupled with smarter connectivity, can facilitate accessibility, assist the recovery and place the economies of the ECE region on a more sustainable track.